2018
DOI: 10.1111/afe.12317
|View full text |Cite
|
Sign up to set email alerts
|

Freeze stress of deciduous trees induces attacks by opportunistic ambrosia beetles

Abstract: 1 A broad host range and the utilization of living but weakened trees contribute, in part, to the invasion success of ambrosia beetles (Curculionidae: Scolytinae). The present study assessed the capability of freeze stress to induce attacks by ambrosia beetles. 2 Freeze stress predisposed Cercis canadensis L., Cornus florida L., Malus pumilaMill. and Styrax japonicus Sieb. to attack under field conditions, although no attacks occurred on untreated trees. More attacks occurred on freeze-stressed versus flood-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 64 publications
1
22
0
1
Order By: Relevance
“…Thus, it is unclear what species of ambrosia beetles were responsible for tree attacks within these regions. Still, previous dissections of experimentally-stressed trees found that Xylosandrus crassiusculus (Motschulsky) and X. germanus were the dominant species recovered in Virginia [13,26,36]; Cnestus mutilatus and X. crassiusculus were the dominant species recovered in Tennessee [37]; and Hypothenemus dissimilis (Zimmermann), Xylosandrus compactus (Eichhoff), and X. crassiusculus were the dominant species in Mississippi [36]. Differences in the seasonal activity and composition of Xyleborine ambrosia beetles could account for variability in efficacy of the insecticide treated netting observed between years and locations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, it is unclear what species of ambrosia beetles were responsible for tree attacks within these regions. Still, previous dissections of experimentally-stressed trees found that Xylosandrus crassiusculus (Motschulsky) and X. germanus were the dominant species recovered in Virginia [13,26,36]; Cnestus mutilatus and X. crassiusculus were the dominant species recovered in Tennessee [37]; and Hypothenemus dissimilis (Zimmermann), Xylosandrus compactus (Eichhoff), and X. crassiusculus were the dominant species in Mississippi [36]. Differences in the seasonal activity and composition of Xyleborine ambrosia beetles could account for variability in efficacy of the insecticide treated netting observed between years and locations.…”
Section: Discussionmentioning
confidence: 97%
“…Xylosandrus germanus is a dominant exotic species in Ohio and upper Midwestern US [5], but the distribution of A. maiche has increased since first being reported in North America in 2009 [34,35]. The incidence of A. maiche in experimentally-stressed trees deployed in Ohio has also increased [12,13,36]. Notably, caution must be taken to accurately distinguish between A. maiche and X. germanus since their morphology is very similar, except the procoxae of A. maiche are contiguous [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change within Europe [119,120], and specifically mild winters, could be assisting the spread of X. germanus. Similarly, freeze stress events following mild winters could also increase the availability of suitable host material and lead to an increased incidence of attacks [97,98]. Heavy precipitation and flood stress can also predispose trees to attack.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of stressors can induce the emission of ethanol from living but weakened trees, including flood and drought stress, freeze stress, girdling, impaired root function, root and crown disturbance, pollutants, and pathogens [92][93][94][95][96]. In particular, flood stress and freeze stress have been demonstrated to induce the emission of ethanol and predisposes trees to attack by ambrosia beetles [85,[96][97][98][99]. The emission of ethanol from aging logs also attracts and induces attacks by X. germanus and other ambrosia beetles [46,67,[100][101][102][103].…”
Section: Host Selection and Preferencementioning
confidence: 99%